Friction-Induced Skin Injuries—Are They Pressure Ulcers? An Updated NPUAP White Paper. Issue 1 (January 2015) - Brienza, David; Antokal, Steven; Herbe, Laura; Logan, Susan; Maguire, Jeanine; Van Ranst, Jennifer; Siddiqui, Aamir
<x xml:space="preserve">Abstract</x> Friction injuries are often misdiagnosed as pressure ulcers. The reason for the misdiagnosis may be a misinterpretation of classic pressure ulcer literature that reported friction increased the susceptibility of the skin to pressure damage. This analysis assesses the classic literature that led to the inclusion of friction as a causative factor in the development of pressure ulcers in light of more recent research on the effects of shear. The analysis in this article suggests that friction can contribute to pressure ulcers by creating shear strain in deeper tissues, but friction does not appear to contribute to pressure ulcers in the superficial layers of the skin. Injuries to the superficial layers of the skin caused by friction are not pressure ulcers and should not be classified or treated as such.